Experimental study of the effects of gas adsorption on the mechanical properties of coal. (1st December 2020) - Zhou, Wei; Gao, Kui; Xue, Sheng; Han, Yunchun; Shu, Chi-Min; Huang, Ping
Abstract: A coupled gas-solid testing system was developed to quantitatively investigate the effects of gas adsorption on the strength, volumetric strain, and fracture development of coal. Uniaxial loading tests were conducted on coal with samples that had adsorbed helium (He), nitrogen (N2 ), methane (CH4 ), and carbon dioxide (CO2 ) gases. Gas adsorption during the testing process was graphed using MATLAB, and the fractal dimensions of the fractures in coal were obtained. Under the same adsorption pressure, the adsorption capacity and degradation rate of coal were found to decrease in the following order for the four gases: CO2 > CH4 > N2 > He. The adsorption of CO2 had a salient negative affect on coal strength, while the effect of non-adsorptive He was negligible. The peak strength decreased by 48.27% after CO2 adsorption at a pressure of 2.0 MPa, and the deterioration rate of coal strength increased logarithmically under adsorption equilibrium pressure. The fractal dimension and density of coal fractures increased with adsorption capacity. The degree of fracture development in coal with adsorbed CO2 at a gas pressure of 2.0 MPa was 2.28-fold that of coal without adsorbed gas, and fish scale-shaped swelling and shedding were observed. The novel findings of this study provided a scientific basis for the quantitative evaluation of the mechanical properties of coal with adsorbed gases.